Neglected Paraphimosis with Hemorrhagic Mucosal Suffusion that Develops into Glans Penile Necrosis : A Rare Case Report - Himawan, Herinto; Yudha, Fajar Gemilang Purna; Wibowo, Donny Austine (Jurnal Ners, 2024)
Paraphimosis is an urological emergency which the narrow end of the prepuce is pulled up over the glans penis, compressing the shaft of the penis and causing pain and swelling of the penis. 1 This condition can cause ischemia in the area distal to compression and lead to tissue necrosis. 2 We present a rare case report of Neglected Paraphimosis with Hemorhagic Mucosal Suffusion that Develops into Glans Penile Necrosis. 13 years old boy with medical history of autism spectrum disorder come to hospital with chief complaint of Hemorhagic Mucosal Suffusion and edema in the glans penis. Physical examination showed Hemorhagic Mucosal Suffusion that surrounding sulcus coronarius and swollen glans penis. Blood clot evacuation was performed and necrosis was seen in the area covered by the blood clot to the glans penis. Penectomy and urethra reconstruction was performed because there is no viable tissue in the distal of the Hemorhagic Mucosal Suffusion. Paraphimosis is an urological emergency that typically affects uncircumcised children and adult. If the problem is not treated effectively, it can develop to infection and vascularization compromise, which can lead to glans necrosis. Necrosis of the glans as a consequence of paraphimosis is an uncommon occurrence. As stated in various situations, the management in dealing with paraphimosis that develop into glans necrosis is variable and corresponds to the clinical condition of the patient. Paraphimosis is a urological emergency that must be managed right away because delay in treatment can cause necrosis. the management in dealing with paraphimosis that develop into glans necrosis is variable and corresponds to the clinical condition of the patient. Keywords: Paraphimosis, glans necrosis, glans edema, neglected paraphimosis, glans hemorhagic